1988
DOI: 10.1136/thx.43.3.206
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermic protection (26-25 degrees C) without perfusion cooling for surgery of congenital cardiac defects using prolonged occlusion.

Abstract: Open heart surgery was performed without perfusion under deep hypothermia in 343 patients with congenital heart defects aged from 1 year 3 months to 44 years. Cooling to a temperature of 26-250C in the oesophagus was achieved by covering the body with crushed ice. The patients were maintained under superficial ether narcosis and they were given morphine (0 5 mg/kg) and tubocurarine (0-5-1l0 mg/kg). The duration of circulatory arrest was 30 minutes in 190 and longer in 153 patients-60-77 minutes in 10 patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 2 publications
(1 reference statement)
0
7
0
Order By: Relevance
“…Systemic hypothermia with or without circulatory arrest continues to be used for cardiac protection during pediatric heart surgery; it has been reported that in the neonatal heart, hypothermia permits a "safe" ischemic period for at least 90 min (107). Despite this, clinical studies have reported a 10% mortality using deep (15°C) hypothermia, with 50% of these deaths ascribed to acute cardiac insufficiency (111). It would appear, therefore, that not all hearts are afforded equal protection by hypothermia.…”
Section: Cardioplegiamentioning
confidence: 99%
“…Systemic hypothermia with or without circulatory arrest continues to be used for cardiac protection during pediatric heart surgery; it has been reported that in the neonatal heart, hypothermia permits a "safe" ischemic period for at least 90 min (107). Despite this, clinical studies have reported a 10% mortality using deep (15°C) hypothermia, with 50% of these deaths ascribed to acute cardiac insufficiency (111). It would appear, therefore, that not all hearts are afforded equal protection by hypothermia.…”
Section: Cardioplegiamentioning
confidence: 99%
“…This is due to progress in cardiac surgery in general as well as changes we have adopted over the years. 12,13 Due to relatively higher mortality in the group with highrisk congenital heart defects in the past, we now operate on these patients under cardiopulmonary bypass. 12,13 It is apparent that the number of operations has reduced in recent years and this is due to our policy of operating under hypothermia only on selected patients, such as those with uncomplicated acyanotic congenital heart lesions, a body weight between 10 and 65 kg, and anticipated circulatory arrest time < 60 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…In stage II, when the esophageal temperature reaches 24°C to 28°C, the actual tympanic temperature drops a further 6°C to 7°C, which provides anti-hypoxic protection of the brain for 60 minutes or more during the circulatory arrest period. 12,13 To prevent cerebral venous congestion, all intravenous fluids were administered through the femoral vein during aortic occlusion. In 4 patients who had circulatory arrest of more than 60 minutes (76 minutes in one case), the cardiac restoration time was quick, and they did not show any neurological deficit postoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations